2008
DOI: 10.1086/586909
|View full text |Cite
|
Sign up to set email alerts
|

An Empathy-Helping Perspective on Consumers' Responses to Fund-Raising Appeals

Abstract: The research examines viewers' actual responses to four televised fund-raising drives by a public television station over a 2-year period. The 584 pledge breaks we studied contain 4,868 individual appeals that were decomposed into two underlying dimensions based on the empathy-helping hypothesis: the appeal beneficiary (self versus other) and emotional valence (positive versus negative). We find that the most effective fund-raising appeals communicate the benefits to others rather than to the self and evoke ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
163
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(189 citation statements)
references
References 40 publications
13
163
0
5
Order By: Relevance
“…For example, an advertisement can try to persuade readers either by appealing to emotions or by appealing to facts and logic (Erlandsson, Västfjäll, Sundfelt, & Slovic, 2016). Advertisements also differ in to what extent they tend to focus on consequences for others or consequences for oneself if complying or not complying (e.g., Fisher, Vandenbosch, & Antia, 2008). Although commercial advertising mostly emphasizes consequences for the reader, advertising by charitable organizations tends to primarily focus on consequences for the victims in plight and only indirectly on the consequences for the donor.…”
Section: Definition Of Negative and Positive Appealsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an advertisement can try to persuade readers either by appealing to emotions or by appealing to facts and logic (Erlandsson, Västfjäll, Sundfelt, & Slovic, 2016). Advertisements also differ in to what extent they tend to focus on consequences for others or consequences for oneself if complying or not complying (e.g., Fisher, Vandenbosch, & Antia, 2008). Although commercial advertising mostly emphasizes consequences for the reader, advertising by charitable organizations tends to primarily focus on consequences for the victims in plight and only indirectly on the consequences for the donor.…”
Section: Definition Of Negative and Positive Appealsmentioning
confidence: 99%
“…In a field study by Chou and Murnighan (2013, Study 1), describing blood donations as a way to "prevent a death" elicited a higher actual blood donation rate than describing it as a way to "save a life," and in a lab study by the same authors (Study 2) it was found that people reading a loss-framed request agreed to volunteer more for poor families than those reading a gain-framed request. One study investigating actual responses to televised charity drives showed that compared to neutral appeals, appeals focusing on the negative consequences for others in a case of not helping increased the number of calls the most (Fisher et al, 2008). The same pattern was found by Haynes et al (2004; self-rated donation-and volunteering-intentions toward animal charities), Burt and Strongman (2005; hypothetical willingness to donate to organizations helping children affected by war) and by Chang (2011; purchase intentions in a study about causerelated marketing).…”
Section: Negative Appeals Are More Effectivementioning
confidence: 99%
“…Salesperson's intellectual understanding of their customers' situation (perspective-taking) and their ability to sense, process, and respond to their customers' feelings (empathic concern) Dawson, Soper, and Pettijohn (1992) Interpersonal process Process of understanding the client's needs Fisher, Vandenbosch, and Antia (2008) Experience, emotional response Emotional response congruent with the perceived welfare of another Giacobbe et al (2006) Ability, comprising cognitive and affective components Ability of salespeople to spontaneously adopt the perspective of their customers through intellectual apprehension of their mental state or condition and by generating a genuine feeling of concern for the customer Homburg, Wieseke, and Bornemann (2009) Ability, cognitive phenomenon Ability to understand and identify with the perspective of the customer Lamont and Lundstrom (1977) Ability, comprising an emotional and a cognitive dimension A salesperson's ability to feel as the other person does to enhance the ability to sell a product or service Pilling and Eroglu (1999) Ability, comprising an emotional and a cognitive dimension…”
Section: Effects Of Empathy In Service Encountersmentioning
confidence: 99%
“…The goal of helping behaviour is thus to enhance the welfare of others. For some kinds of behaviour, such as organ donation (e. g., Morgan and Miller, 2002), these altruistic reasons are evident and, consequently, a message with a help-others appeal (or other-benefit appeal; Fisher, Vandenbosch, and Antia, 2008) stressing the benefits for others may be deemed appropriate. However, readers may also be guided by other than altruistic motives, such as when a cause is personally relevant (e. g., a reader who has experienced heart problems), or will become personally relevant in the future (e. g., environmental issues).…”
Section: Help-others and Help-self Appeals Adapted To Gendered Valuesmentioning
confidence: 99%